READING HABIT AND WRITING ABILITY: THE CORRELATION - I Komang Adi Jaya Sentana; Luh Ketut Sri Widhiasih; Nengah Dwi Handayani (Academic Journal on English Studies (AJOES), 2023)
This correlational research aims at finding out the correlation between habit of reading and writing ability of tenth grade students when learning narrative text. Some tenth grade students of SMAK Harapan Denpasar was taken as samples (60 students from two classes). In collecting the data, the researcher used five Likert scales questionnaire and writing narrative text test. The data collected in this research were analyzed by Pearson product moment and t - testing using SPSS version 25 for Windows. According to the result of the analysis and statistical calculation, it is found that r was 0.480. It also shows that the correlation between students reading habit and their ability of writing narrative text of tenth grade lies between 0.401-0.600 which is medium level. Moreover, the data shows significant correlation between both variables (t was 36.097). From the result, it can be concluded that there is significant correlation between reading habit and writing ability. Furthermore, the students and teachers should pay attention to the result of this reseach to increase the writing ability by increasing the reading habit of the students. It can be done by choosing various interesting and uptodate materials and strategies.